A strong convergence result involving an inertial forward–backward algorithm for monotone inclusions - Dong, Qiaoli; Jiang, Dan; Cholamjiak, Prasit; Shehu, Yekini (Fixed point theory and algorithms for sciences and engineering, 2017)
Our interest in this paper is to prove a strong convergence result for finding a zero of the sum of two monotone operators, with one of the two operators being co-coercive using an iterative method which is a combination of Nesterov’s acceleration scheme and Haugazeau’s algorithm in real Hilbert spaces. Our numerical results show that the proposed algorithm converges faster than the un-accelerated Haugazeau’s algorithm.